A French regulatory edge [Internet regulations]. - Sweet, W. (IEEE spectrum)
The US telecommunications equipment maker, Lucent Technologies Inc., has merged with the French company, Alcatel SA, with the latter playing the more dominant role due in part to the French government's emphasis on advanced Internet technologies. The merger compels Alcatel to open its system to competing providers of broadband services, resulting to lower television, telephony and Internet access rates while giving a boost to national phone companies and their dominant equipment suppliers.